An innovative approach to assess comprehensive care: Temple University's patient wellness report. Issue 5 (24th December 2020) - Tellez, Marisol; Meraner, Mark; Lim, Sungwoo; Brandon, Ryan; Ismail, Amid
Abstract: Purpose: The transition from a paper‐based to an all‐electronic patient health record took a major step forward in 2018, with the implementation of an electronic health record that supports the School's patient‐centered comprehensive care model and facilitates outcomes assessment. The Patient Wellness Report (PWR) summarizes findings of the patient assessment, and it does so automatically by locating data already entered in axiUm forms. This study aimed to describe the PWR implementation procedures and to examine outcomes and characteristics among patients with completed treatment plans during an 18‐month period. Methods: Outcome data were extracted from axiUm for patients aged ≥16 years who completed comprehensive care treatment plans. Each PWR contained 14 metrics related to "dimensions" of wellness (quality of life, general health factors, oral hygiene, caries risk, and degree of periodontal inflammation and pocketing), each of which is rated on a 3‐point scale based on best available scientific evidence. Results: A total of 2074 patients completed planned procedures between July 2018 and January 2020, and met the study eligibility criteria. Improvement of several conditions was observed between baseline and follow‐up in caries lesions (21%), blood pressure (9%), and periodontal pocket (3.2%). A majority of patients rated in good condition at baseline had their scores unchanged at follow‐up in the following areas: dental anxiety (92%), speaking (88%), smoking (87%), and alcohol consumption (79%). Conclusion: Improvements in dental caries and blood pressure metrics were easily monitored using the PWR. In addition, disparities exist in improvement of patient outcomes by race/ethnicity.